Neuroinflammatory Biomarkers Associated With Mild Traumatic Brain Injury History in Special Operations Forces Combat Soldiers. Issue 5 (September 2020) - Powell, Jacob R.; Boltz, Adrian J.; DeCicco, Jamie P.; Chandran, Avinash; DeLellis, Stephen M.; Healy, Marshall L.; Kane, Shawn F.; Lynch, James H.; Means, Gary E.; Hackney, Anthony C.; Mihalik, Jason P.
Abstract : Background: Special Operations Forces (SOF) combat soldiers are frequently exposed to blast and blunt neurotrauma, most often classified as mild traumatic brain injury (mTBI). Repetitive mTBI may increase the risk of developing long-term neurological sequelae. Identifying changes in neuroinflammatory biomarkers before chronic conditions emerge could serve as preliminary evidence of developing neuropathology. Objective: To determine the effects of mTBI history, lifetime mTBI incidence, and recency on blood biomarker concentrations of axonal protein neurofilament light (NfL), glycolytic enzyme neuron-specific enolase (NSE), astrocyte-expressed S100 calcium-binding protein B (S100B), and neurotrophic cytokine interleukin-6 (IL-6) in healthy, active duty SOF combat soldiers. Methods: Self-reported mTBI history/recency and fasted blood samples were collected in this cross-sectional study of 104 asymptomatic SOF combat soldiers. Biomarker concentrations were quantified using commercial enzyme-linked immunosorbent assays. Mann-Whitney U and Kruskal-Wallis tests were used to compare groups. Post hoc tests with appropriate corrections were conducted as warranted. Results: Soldiers with mTBI history had higher NSE concentrations than those without ( z = −2.60, P = .01). We also observed significant main effects of lifetime mTBI incidence on NSE (χ 2 (3) = 9.52, P = .02) and S100B (χ 2 (3) = 8.21, P = .04) concentrations and a significant main effect of mTBI recency on NfL concentration (χ 2 (2) = 6.02, P = .049). Conclusion: The SOF combat soldiers with mTBI history had increased NSE. Longitudinal studies in this population are needed due to between-subject heterogeneity in biomarker concentrations. The NfL concentrations in our SOF combat soldiers—regardless of mTBI history or recency—were similar to values previously reported in civilian acute TBI patients. Abstract : Supplemental Digital Content is Available in the Text.